Influence Knowledge Tax and Quality Service to Obedience Must Taxes at KPP Pratama South Makassar - Utami Pradana Putri; Sahade Sahade; M. Ridwan Tikollah; Nur Afiah; Abd Rijal (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of tax knowledge and service quality on individual taxpayer compliance at KPP Pratama South Makassar. The variables in this study are Tax Knowledge (X1) and Service Quality (X2) as independent variables and Individual Taxpayer Compliance (Y) as the dependent variable. The population in this study were all individual taxpayers registered at the South Makassar KPP Pratama. The sample was selected using the slovin formula and produced 100 individual taxpayers as the sample. The data collection technique used is a questionnaire. Data analysis techniques used are classical assumption tests, data quality tests, multiple linear regression analysis and hypothesis testing. The results showed that partially tax knowledge had no effect on taxpayer compliance and service quality had an effect on taxpayer compliance at the South Makassar KPP Pratama . Simultaneously, tax knowledge and service quality have no effect on taxpayer compliance at the South Makassar KPP Pratama .